EVALUASI KINERJA PEMERIKSA PAJAK DI KANTOR PELAYANAN PAJAK (KPP) PRATAMA MAGELANG (Jurnal Riset Mahasiswa, 2023)
This study uses a descriptive qualitative approach. The informants used in this study were 3 people consisting of 1 Head of Audit Section and 2 tax auditors at KPP Pratama Magelang. Data analysis uses interactive model data as proposed by Miles and Huberman (2002) which includes three components, including data reduction, data presentation, conclusion drawing or verification. The performance of the Tax Auditor at KPP Pratama Magelang is still not optimal, the reason being that there are several obstacles in the implementation of the tax audit, namely: multi-interpretation tax regulations; high routine inspection load; revenue targets are too high; lack of quantity and quality of Tax Auditor Functional; and the lack of support for official vehicles and operational funds in the implementation of tax audits. Efforts to improve the performance of tax auditors at KPP Pratama Magelang are tax regulations must be prepared by taking into account the principles of clarity, certainty and simplicity so as to minimize the emergence of different interpretations (multi interpretation); additional quantity and quality of Tax Auditor Functional; improving tax services both directly and online; and provision of official vehicles for the implementation of audits and separation of operational tax audit funds.
Keywords: evaluation; performance; tax examiner